THE ROLE OF TEACHERS IN PROMOTING INFORMATION LITERACY A SOCIOLOGICAL PERSPECTIVE - Maranoor, Rajashree S (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The importance of teachers in promoting information literacy has grown in the digital age. Teachers act as vital mediators, helping students make sense of the deluge of information they are navigating by giving them the tools they need to critically assess, understand, and apply what they have learned. The sociological aspects of teachers’ roles in fostering information literacy are examined in this study, with a focus on how they affect students’ academic performance, habits of lifelong learning, and digital citizenship. Through an examination of pedagogical approaches, institutional assistance, and societal norms, the study underscores the obstacles and possibilities educators encounter in fostering an information-literate community. The results highlight the necessity of curriculum integration, professional development initiatives, and legislative changes to improve teachers’ efficacy in this area.